SRATEGI PENGELOLAAN KONTEN “F BEAUTY STANDARD” DALAM MEMBAGUN E-WOM PADA AKUN INSTAGRAM @madformakeup.co - Millenia Farizqi, Aurel; Istia Wahyuni, Itca (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
In the era of digital activity, word of mouth is mediated by the presence of the internet, which is known as electronic word of mouth. Developments continue to occur, so many companies are using electronic word of mouth as their communication strategy. One company in the beauty sector, Mad for Makeup, utilizes the content of 'F Beauty Standard' as a strategy in building electronic word of mouth. This study aims to determine the content management strategy of 'F Beauty Standard' in building electronic word of mouth on the Instagram account @madformmakeup.co. The method used in this research is qualitative with descriptive approach, using constructivism paradigm. In collecting data, the researcher conducted semi-structured in-depth interviews with key informants and experts. The key informants in this study were the Co-Founder, External Communications Manager, Content Manager, Internal Communication Manager Mad for Makeup, and expert informants in the field of digital marketing. The results showed that in the strategic planning stage, the Mad for Makeup audience was determined by the category of students to first jobbers. At the implementation stage, Mad for Makeup manages content using hashtags, sees post insights, and establishes interaction between audiences in building electronic word of mouth. At the evaluation stage, Mad for Makeup conducted a content analysis of the 'F Beauty Standard' data to improve content management activities in the future